2016
DOI: 10.1111/ejh.12734
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of liver iron concentration by superconducting quantum interference device biomagnetic liver susceptometry validates serum ferritin as prognostic parameter for allogeneic stem cell transplantation

Abstract: Our data confirmed that SF ≥1000 increases the risk of infection, moreover fungal infection in transplant recipients. As SQUID values correlate well with SF, we could show that SF is indeed a good surrogate parameter for iron overload when measured shortly before SCT. Prospective trials are needed to investigate the effect of iron chelation before or during SCT on transplant outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…A disadvantage is that SF is an acute phase protein; therefore, SF levels may also be impacted by events such as tissue injury and inflammation. Despite this, SF has been a frequent assessment in clinical trials, and an SF level of ≥ 1,000 ng/mL has recently been validated as a marker of IO and poor prognosis following ASCT (Jacobi & Herich, 2016). In this study, iron levels as measured by a superconducting quantum interference device (SQUID) correlated highly with SF levels (r = .6; p < .001), and SF was predictive of worse overall and event-free survival (Jacobi & Herich, 2016).…”
Section: Current Methods For Diagnosis Of Iron Overloadmentioning
confidence: 79%
See 2 more Smart Citations
“…A disadvantage is that SF is an acute phase protein; therefore, SF levels may also be impacted by events such as tissue injury and inflammation. Despite this, SF has been a frequent assessment in clinical trials, and an SF level of ≥ 1,000 ng/mL has recently been validated as a marker of IO and poor prognosis following ASCT (Jacobi & Herich, 2016). In this study, iron levels as measured by a superconducting quantum interference device (SQUID) correlated highly with SF levels (r = .6; p < .001), and SF was predictive of worse overall and event-free survival (Jacobi & Herich, 2016).…”
Section: Current Methods For Diagnosis Of Iron Overloadmentioning
confidence: 79%
“…Despite this, SF has been a frequent assessment in clinical trials, and an SF level of ≥ 1,000 ng/mL has recently been validated as a marker of IO and poor prognosis following ASCT (Jacobi & Herich, 2016). In this study, iron levels as measured by a superconducting quantum interference device (SQUID) correlated highly with SF levels (r = .6; p < .001), and SF was predictive of worse overall and event-free survival (Jacobi & Herich, 2016). Another study suggested that SF is a reasonable surrogate to detect IO in patients undergoing ASCT, although the authors propose increasing the threshold to 2,500 ng/mL (Armand et al, 2011).…”
Section: Current Methods For Diagnosis Of Iron Overloadmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate ratio for fungal infections remained unchanged after adjustment for aGVHD grades II-IV (RR 5 2.76, 95% confidence interval [CI] 1.1–6.7, P 5 .01), indicating there was no evidence of confounding by aGVHD. Another important risk factor advocated for an increased peritransplant mortality, and in particular due to the infections is the iron overload 86 91 The ferritinemia (SF) is considered the standard method for measuring iron overload. However, the optimal parameters and time points for the measurement of iron overload (IO) in allogeneic stem cell transplantation (ASCT) patients are still under discussion.…”
Section: Intermediate 2 and High Risk Mdsmentioning
confidence: 99%
“…SF is commonly used as a marker of iron overload (defined as SF ≥1000 ng/mL) [1], but this role has been often questioned, as SF value can be affected by acute infections, inflammations, and even malignant conditions, so that it is also considered as an acute phase protein. Several studies have evaluated tests other than the evaluation of SF level to estimate iron overload, such as Magnetic Resonance Imaging (MRI) and Superconducting Quantum Interference Device (SQUID) biomagnetic liver susceptometry [24]; however, SF is still considered the most adequate surrogate parameter for body iron overload concentration, as recently confirmed [4]. …”
Section: Introductionmentioning
confidence: 99%